Claudin-18 expression under hyperoxia in neonatal lungs of bronchopulmonary dysplasia model rats - Zuo, Jingye; Tong, Yajie; Yang, Yuting; Wang, Yirui; Yue, Dongmei (Frontiers in Pediatrics, 2022)
Background Bronchopulmonary dysplasia (BPD) is characterized by impaired alveolar and microvascular development. Claudin-18 is the only known lung-specific tight junction protein affecting the development and transdifferentiation of alveolar epithelium. Objective We aimed to explore the changes in the expression of claudin-18, podoplanin, SFTPC, and the canonical WNT pathway, in a rat model of hyperoxia-induced BPD, and to verify the regulatory relationship between claudin-18 and the canonical WNT pathway by cell experiments. Methods A neonatal rat and cell model of BPD was established by exposing to hyperoxia (85%). Hematoxylin and eosin (HE) staining was used to confirm the establishment of the BPD model. The mRNA levels were assessed using quantitative real-time polymerase chain reaction(qRT-PCR). Protein expression levels were determined using western blotting, immunohistochemical staining, and immunofluorescence. Results As confirmed by HE staining, the neonatal rat model of BPD was successfully established. Compared to that in the control group, claudin-18 and claudin-4 expression decreased in the hyperoxia group. Expression of β-catenin in the WNT signaling pathway decreased, whereas that of p-GSK-3β increased. Expression of the AEC II marker SFTPC initially decreased and then increased, whereas that of the AEC I marker podoplanin increased on day 14 (P < 0.05). Similarly, claudin-18, claudin-4, SFTPC and β-catenin were decreased but podoplanin was increased when AEC line RLE-6TN exposed to 85% hyperoxia. And the expression of SFTPC was increased, the podoplanin was decreased, and the WNT pathway was upregulated when claudin-18 was overexpressed. Conclusions Claudin-18 downregulation during hyperoxia might affect lung development and maturation, thereby resulting in hyperoxia-induced BPD. Additionally, claudin-18 is associated with the canonical WNT pathway and AECs transdifferentiation.